The role of interleukin 22 in multiple sclerosis and its association with c-Maf and AHR - Zarobkiewicz, Michal Konrad; Kowalska, Wioleta; Slawinski, Miroslaw; Rolinski, Jacek; Bojarska-Junak, Agnieszka (Biomedical papers, 2019)
The aim of this paper was to summarise knowledge of IL-22 involvement in multiple sclerosis (MS) and the possible link between IL-22 and two transcription factors - AHR and c-Maf. The conclusion is that despite numerous studies, the exact role of IL-22 in the pathogenesis of MS is still unknown. The expression and function of c-Maf in MS have not been studied. It seems that the functions of c-Maf and AHR are at least partly connected with IL-22, as both directly or indirectly influence the regulation of IL-22 expression. This possible connection has never been studied in MS.
Keywords: multiple sclerosis; IL-22; transcription factors; c-Maf; AHR; EAE